GUILLAIN-BARRÉ SYNDROME (REMUNOM, 2025)
Guillain-Barré Syndrome (GBS) is an autoimmune pathology characterized as an acute inflammatory polyradiculoneuritis of rapid progression, which results in the loss of myelin from peripheral nerves. Its main complication is ascending muscle weakness, the cause of which is not yet fully known. However, there is strong evidence of a correlation with the existence of a previous infectious process, whether viral or bacterial. It is a very worrying pathology, since such ancestry tends to compromise the respiratory muscles, thus hindering the process of full recovery without complications associated with the condition. It is a rare pathology that for a long time was believed to be purely demyelinating, but currently axonal forms of the disease are recognized, responsible for a range of physiological complications and autonomous functions. This is a qualitative research that used bibliographic review as an instrument to search for information. The search was carried out in the databases Scientific Electronic Library Online (SCIELO), PubMed, Periódicos CAPS and search engine sites through Scholar Google. Through the bibliographical research carried out, answers were established to the objective of the article, which is to inform future health professionals and nurses, what are the attitudes, skills and systematization of nurses' care for patients with Guillain-Barré Syndrome.